Effect of multi-geometrical laser pattern of Ti6Al4V on frictional wear behaviour - Mohd Harizan, Zul; Mahadzir, Ishak; Ramdziah, Md Nasir; Aiman, Mohd Halil; Moinuddin, Mohammed Quazi (Malaysian Tribology Society (MYTRIBOS), 2024)
This research paper aims to investigate the impact of multi-geometrical patterns resulting from laser texturing of Ti6Al4V on friction and wear characteristics. The methodology involved laser texturing of the Ti6Al4V material with a laser power of 12 W, laser frequency of 40 kHz, and a laser scan speed of 180 mm/s. A frictional sliding wear test was performed using reciprocating motion with Si3N4 balls as counterparts. The sliding conditions were a load of 10 N, speed of 75 m/min, and duration of 30 minutes. The tests were conducted in three environments: dry, artificial seawater, and engine oil. The results indicate that the circle pattern performs better in dry conditions, while the grid pattern exhibits enhanced wear resistance by 75% in oil environments compared to dry conditions. Therefore, the geometrical pattern created by laser texturing has a significant impact on the tribological performance of Ti6Al4V material under various sliding conditions. These findings could have potential implications for improving the wear and frictional behavior of Ti6Al4V in different environments.